The Use of TikTok Media on the Knowledge of Dental and Oral Hygiene among Students of SMAN 1 Porong - Nur Fauziyah; Imam Sarwo Edi; Siti Fitria Ulfah; Silvia Prasetyowati (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2026)
Oral and dental hygiene remains a significant public health concern among adolescents, largely due to inadequate knowledge and limited exposure to effective health education. Preliminary findings at SMAN 1 Porong indicated that 50% of students exhibited poor plaque indices, reflecting insufficient awareness of proper oral hygiene practices. This study aimed to evaluate the effectiveness of TikTok-based educational media in improving students’ knowledge of oral and dental hygiene. A quasi-experimental design with a one-group pretest–posttest approach was employed. A total of 52 tenth-grade students were selected using simple random sampling. Data were collected through a structured questionnaire distributed via Google Forms before and after the intervention. The educational intervention consisted of delivering oral health content through TikTok media. Data analysis was conducted using the Wilcoxon Signed-Rank Test to assess differences in knowledge scores before and after the intervention. The results demonstrated a substantial improvement in students’ knowledge following the intervention. Prior to education, 96% of respondents were categorized as having low knowledge, whereas after the intervention, 88% achieved a good knowledge level. Statistical analysis revealed a significant difference between pretest and posttest scores (p = 0.000; p < 0.05), indicating the effectiveness of TikTok as an educational medium. In conclusion, TikTok-based health education significantly enhances adolescents’ knowledge of oral and dental hygiene. The findings suggest that integrating social media platforms into health promotion strategies can serve as an innovative and engaging approach to improve health literacy among students. Future research is recommended to explore the long-term impact of such interventions and to compare the effectiveness of different digital media platforms.